Sound at the Edge of Perception The Aural Minutiae of Sand and other Worldly Murmurings - Street, Seán.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Pivot, 2019)
This book is about the tiny sounds of the world, and listening to them, the minute signals that are clues to who and where we are. A very small sound, given the context of its history, becomes hugely significant, and even an imagined sound in a picture becomes almost a voice. By speaking a name, we give a person back to the world, and a breath, a sigh, a laugh or a cry need no language. A phoneme is the start of all stories, and were we able to tune ourselves to the subtleties of the natural world, we might share the super-sensitivity of members of the bird and animal kingdom to sense the message in the apparent silence. Mind hears sound when it perceives an image; the book will appeal to sonic and radio practitioners, students of sound, those working in the visual arts, and creative writers.
1 Introduction: The Bell of Józef Czechowicz ¬- The Importance of Minute Sound Moments -- 2 The Notes of Human Music -- 3 Making the Moment Singable -- 4 Signals from Near and Far Shores - Voices from the Natural World -- 5 Speak My Name - the Ownership of Syllables -- 6 First and Last Sounds - Messages Beyond Language.
Keywords: Science -- Social aspects; Music; Science and Technology Studies; Music